Are better young readers more likely to confuse their mother with their mohter?. Issue 9 (September 2021) - Gomez, Pablo; Marcet, Ana; Perea, Manuel
One of the most replicated effects in the contemporary word recognition literature is the transposed-letter effect (TL effect): pseudowords created by the transposition of two letters (e.g., MOHTER) are often misread as the real word. This effect ruled out those accounts that assume that letter position is encoded accurately and led to more flexible coding schemes. Here, we examined whether reading skill modulates this effect. The relationship between reading skill and the TL effect magnitude is a contentious issue both empirically and theoretically. The present lexical decision experiment was designed to shed some light on the relationship between reading skill and the TL effect magnitude with a large sample of Grade 6 children. To that end, we conducted both multiple regression and path analyses. Results showed that a specific aspect of reading skills (pseudoword reading) negatively correlates with the TL effect's magnitude in the error data (i.e., MOHTER is less wordlike for better readers). This finding highlights the need for a comprehensive visual-word recognition model that includes individual variability and the multidimensional character of reading in school-age children.